2020
DOI: 10.3390/rs13010110
|View full text |Cite
|
Sign up to set email alerts
|

Sea Surface Salinity Seasonal Variability in the Tropics from Satellites, Gridded In Situ Products and Mooring Observations

Abstract: Satellite observations of sea surface salinity (SSS) have been validated in a number of instances using different forms of in situ data, including Argo floats, moorings and gridded in situ products. Since one of the most energetic time scales of variability of SSS is seasonal, it is important to know if satellites and gridded in situ products are observing the seasonal variability correctly. In this study we validate the seasonal SSS from satellite and gridded in situ products using observations from moorings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…Interestingly, the R 2 values for in situ products are generally greater than those for satellite products although the harmonic amplitude patterns are all similar. A similar result was also obtained by Bingham et al (2021) in the tropics using mooring data as an in situ comparison. This is especially the case in the extratropical ocean where annual amplitudes in most areas are lower than 0.1 pss.…”
Section: Variances Explained By the Harmonic Modessupporting
confidence: 85%
See 2 more Smart Citations
“…Interestingly, the R 2 values for in situ products are generally greater than those for satellite products although the harmonic amplitude patterns are all similar. A similar result was also obtained by Bingham et al (2021) in the tropics using mooring data as an in situ comparison. This is especially the case in the extratropical ocean where annual amplitudes in most areas are lower than 0.1 pss.…”
Section: Variances Explained By the Harmonic Modessupporting
confidence: 85%
“…It is found that the R 2 values vary with the type of product. The R 2 values for annual harmonic are relatively lower in satellite products, at about 49%-58%, but are higher in in situ products, at about 66%-72% (Bingham et al, 2021). The R 2 values for the semiannual harmonic are more in a more narrow range, at about 15%-19% in all products.…”
Section: Summary and Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…SSS in the tropics tends to be quite spiky, with many low outliers, (e.g. Bingham et al (2021), their Figure 2) Overly stringent quality control could eliminate many valid data points and alter the statistics of the record.…”
Section: Methodsmentioning
confidence: 99%
“…These may take the form of comparisons with gridded Argo products such as that of [5] or [6] ( [2,3,[7][8][9][10][11][12]). There may also be comparisons with individual observations such as floats, saildrones, thermosalinographs or moorings [8][9][10][13][14][15][16][17][18][19][20]. Comparisons may be done using satellite data at level 2 (L2) (e.g.…”
Section: Introductionmentioning
confidence: 99%